Dynamics of microbiota in Japanese Black beef stored for a long time under chilled conditions. (December 2021) - Nakamura, Ayaka; Takahashi, Hajime; Otomo, Kota; Mizuno, Yuri; Kuda, Takashi; Kimura, Bon; Koike, Fumiaki; Kobayashi, Mitsushi
Abstract: In this study, changes in the microbiota of Japanese Black beef carcasses, which are expected to be transported for a long time in chilled temperatures, were investigated. Three Japanese Black beef samples (carcasses A, B, and C) immediately after slaughter were stored at 0 °C for 15 weeks under aerobic and vacuum conditions. The initial bacterial counts were 50 CFU/g for carcass A and less than the reliable quantitative detection limit for carcasses B and C. Under aerobic storage conditions, the bacterial count increased to 8.0 log CFU/g or higher, which is a measure of putrefaction, at 6–9 weeks. Under anaerobic storage conditions, the bacterial counts of carcasses A and C reached 3.5–6.5 log CFU/g, but carcass B showed no bacterial growth during the 15-week storage period. The predominant group was Pseudomonas spp . under aerobic conditions and Serratia spp . under anaerobic conditions. To the best of our knowledge, there is no previous study investigating the transition of microbiota when Japanese Black beef is stored at low temperatures for a long period of time, and the results of this study are considered very important findings for the expansion of international trade of Japanese Beef in the future. Highlights: Dynamics of microflora of beef carcasses stored at 0 °C for 15 weeks was investigated. The initial count of Japanese Black beef carcasses was under 1.7 log CFU/g. Bacterial counts increased to spoilage level at 6–9 weeks under aerobic condition. No bacterial growth was observed in one beef carcass under anaerobic storage period. The predominant group in beef carcasses was Serratia sp . under anaerobic conditions.